The Principal's Role as Education Supervisor in Improving Teacher Professionalism - Chairunnisa Amelia; Andika Aprilianto; Dasep Supriatna; Ibnu Rusydi; Novela Elza Zahari (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2022)
Professional teachers are not only required to master the fields of science, teaching materials, learning methods, and student motivation. They have high skills and broad insight into the world of education. This is inseparable from the guidance of a supervisor. Supervision is carried out to form and improve abilities in the teaching and learning process. Maintenance can help enhance teachers' professional skills so that teachers can carry out the teaching and learning process that they do in class well. Besides that, a teacher can also act as a professional educator in carrying out their duties and responsibilities in guiding and teaching, creating a comfortable learning atmosphere, and good communication. This article aims to describe the role of the principal as a supervisor to assist the teaching profession. The research method used in this article is a qualitative method with a case study approach.